Circularly‐Polarized Electrochemiluminescence from a Chiral Bispyrene Organic Macrocycle. Issue 21 (17th April 2019) - Zinna, Francesco; Voci, Silvia; Arrico, Lorenzo; Brun, Elodie; Homberg, Alexandre; Bouffier, Laurent; Funaioli, Tiziana; Lacour, Jérôme; Sojic, Neso; Di Bari, Lorenzo
Abstract: The first observation of circular polarization of electrochemiluminescence (ECL) from a purely organic derivative is reported. A bispyrene scaffold mounted on a constrained polyether macrocycle displaying intense excimer fluorescence and highly circularly‐polarized (CP) photoluminescence has been selected for this purpose. The compound displays an ECL dissymmetry factor of about |8×10 −3 |, which is in good agreement with the corresponding photoluminescence value. This observation is the first step towards the molecular engineering of tailored dyes that can act as both ECL and CP‐ECL reporters for (bio)analysis by bringing a new level of information when dealing with chiral environments. Additionally, it provides an extra dimension to the ECL phenomenon and opens the way to chiral detection and discrimination. Abstract : A polarizing pair : Circularly polarized electrochemiluminescence from a chiral organic molecule is observed. The macrocyclic scaffold leads to an efficient excimer formation between two pyrene moieties that are covalently attached. As a result, highly polarized emission is obtained upon electrochemical excitation.